Implementation of Guided Imagery and Intradialityc Exercise Regular Flexibility on Fatigue of Hemodialysis Patients - Maria Yulianti; Dhea Natashia; Dewi Gayatri; Diana Irawati; Wati Jumaiyah; Tuti Nuraini (Indonesian Journal of Global Health Research, 2024)
Fatigue is a common symptom in dialysis patients, with a significant prevalence rate. In overcoming the problem of fatigue, therapeutic management is done through the application of guided imagery and intradialytic exercise. Objective: Objective is assess the effect of guided imagery and intradialytic exercise regular flexibility on fatigue in patients with chronic kidney disease who are undergoing hemodialysis process. Methods: The research method used a quasi-experiment with a one group pretest-posttest design without control group approach. The population was 23 respondents with a sample size of 22 respondents using total sampling technique. Measurement of fatigue using Functional Assessment Chronic Illness Therapy (FACIT). Data analysis was performed using paired t-test and Repeated Measures ANOVA. Results: The results showed that the mean value of fatigue before intervention in the first measurement was 24.00 (±3.911). The value increased in the second measurement to 25.22 (±4.095), in the third measurement to 28.11 (±3.411), in the fourth measurement to 33.89 (±2.908), and in the last measurement to 39.67 (±3.106). This finding explained that both interventions had a significant impact on reducing fatigue (t = -18.561, p = 0.000). Time effect analysis confirmed the significant impact of the interventions on fatigue reduction scores (F(1, 473) = 187.798, p < 0.000, partial eta squared = 0.917). Conclusion: This study can be used as a non-pharmacological treatment to reduce fatigue symptoms that can be done independently during the hemodialysis process, and is expected as an independent nursing intervention for a nurse in providing nursing care.